"Cannonballs" and psammoma bodies: Unusual cytologic features of metastatic pulmonary small‐cell carcinoma in a pleural effusion. Issue 3 (11th October 2011) - Conway, Andrea B.; Hart, Melissa K.; Jessurun, Jose; Pambuccian, Stefan E.
Abstract Large three‐dimensional cell aggregates and psammoma bodies are usually encountered in benign serous effusions (mesothelial hyperplasia and endosalpingiosis), mesotheliomas, and metastatic papillary carcinomas. We report a case of pulmonary small‐cell carcinoma occurring in an 88‐year‐old woman that initially presented with a malignant pleural effusion characterized cytologically by a predominance of large three‐dimensional neoplastic cell aggregates ("cannonballs"), associated with rare psammoma bodies. Although the crowded three‐dimensional tumor‐cell aggregates did not allow detailed cytologic examination, the diagnosis of metastatic small‐cell carcinoma could be established noting the characteristic chromatin features of the occasional single neoplastic cells and the characteristic "cell‐in‐cell" and "stack‐of‐coins" arrangements of rare small clusters of neoplastic cells. Immunoperoxidase stains showing positivity of the tumor cells for CD56, synaptophysin, and TTF1 further supported this diagnosis. Endobronchial ultrasound‐guided fine‐needle aspiration of a mediastinal lymph node subsequently confirmed the diagnosis of pulmonary small‐cell carcinoma. Metastatic pulmonary small‐cell carcinoma should be considered in the differential diagnosis of serous effusions showing large three‐dimensional neoplastic cell aggregates and psammoma bodies to prevent a potential diagnostic pitfall. Diagn. Cytopathol. 2013. © 2011 Wiley Periodicals, Inc.